Development of a sea-ice tank system for measuring microwave properties of sea ice - Masashige Nakayama; Kazuhiro Naoki; Tomonori Tanikawa; Kohei Cho (Journal of Glaciology)
An outdoor sea-ice tank system for measuring the microwave properties of sea ice has been developed. With the natural cooling and the help of a cooling unit in the movable roof attached to the tank, the system can grow sea ice to about 50 cm thickness continuously without the effects of snowfall and/or melting. Portable microwave radiometers are attached beside the tank to measure the brightness temperature of the ice. As sea ice grows, the system can measure microwave brightness temperature, and seawater/ice temperature at each depth and thickness of sea ice. The bulk salinity of sea ice is measured by sampling. The following results were obtained from experiments conducted during two winters. (1) Rapid desalination was observed during the early stages of growth with ice thicknesses of 0–5 cm. (2) A new relational expression between ice thickness and bulk salinity at this thickness was obtained. (3) The rapid rise in microwave brightness temperature associated with the increase in sea-ice thickness during the early stages of sea-ice growth was captured in each frequency band. The microwave measurements from the sea-ice tank system are expected to provide new insights into the microwave properties of sea ice.